2023
DOI: 10.1007/s13280-023-01831-6
|View full text |Cite
|
Sign up to set email alerts
|

Our evolved understanding of the human health risks of mercury

Abstract: Mercury (Hg) is a chemical of health concern worldwide that is now being acted upon through the Minamata Convention. Operationalizing the Convention and tracking its effectiveness requires empathy of the diversity and variation of mercury exposure and risk in populations worldwide. As part of the health plenary for the 15th International Conference on Mercury as a Global Pollutant (ICMGP), this review paper details how scientific understandings have evolved over time, from tragic poisoning events in the mid-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 120 publications
(153 reference statements)
0
23
0
Order By: Relevance
“…14,15 MeHg exposure due to gold mining is still a problem in the world, and there is concern about neurological dysfunction due to its neurotoxicity. 58 However, the countermeasures against MeHg neurotoxicity are not yet complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 MeHg exposure due to gold mining is still a problem in the world, and there is concern about neurological dysfunction due to its neurotoxicity. 58 However, the countermeasures against MeHg neurotoxicity are not yet complete.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is induced in the brain by lifestyle modification through moderate exercise 56,57 and is widely known to be involved in the maintenance of neural function 14,15 . MeHg exposure due to gold mining is still a problem in the world, and there is concern about neurological dysfunction due to its neurotoxicity 58 . However, the countermeasures against MeHg neurotoxicity are not yet complete.…”
Section: Discussionmentioning
confidence: 99%
“…Mercury exposure poses profound health risks, especially to neurological functions, with fetuses and young children being vulnerable, and longterm exposure is linked to developmental delays, cognitive impairments, neurological disorders, kidney damage, and cardiovascular issues. [209][210][211] Paulino et al reported a fluorescent chemosensor (22) based on Te-rhodamine units for the rapid detection of Hg 2+ ions in water, utilizing the oxidation of Te induced by mercury ions. 136 Unlike conventional chelationbased chemosensors, 22 demonstrated selectivity for Hg 2+ over other ROS and showed differentiation between Fe 3+ and Hg 2+ .…”
Section: Fluorescent Probes For Metal Ion Sensingmentioning
confidence: 99%
“…Fish and marine mammals are known to be among the primary sources of Hg worldwide (e.g., Evers and Sunderland, 2019), Hg being present in the form of methyl Hg compounds (70%-90% of the total) (WHO, 2000). Despite this knowledge, there is a glaring data deficit on Hg levels in fish and other forms of seafood (Capodiferro et al, 2022;Basu et al, 2023), which underlines the importance of collecting site-specific Hg abundance data in fish and other forms of seafood from around the world, as Hg levels in fish vary widely across and within species (See: UNEP, 2019a). Mercury content of edible fish tissues for various species can vary from 50 to 1,400 ppb fresh weight (IPCS, 2003;Raihan et al, 2020), depending on factors such as pH, the redox potential of the water and the species, age and size of the fish (WHO, 2000).…”
Section: Food Crops and Other Major Dietary Sourcesmentioning
confidence: 99%